Back to the 'normal' level of human-capital driven growth? A note on early numeracy in Korea, China and Japan, 1550 - 1800 - Joerg Baten; Kitae Sohn (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
This paper draws on a unique data set, hojok (household registers), to estimate numeracy levels in Korea, 1550-1630, and evidence on Japan and China from the early modern period until 1800. We found that a substantial share of East Asians rounded their ages to multiples of five. However, the extent of age-heaping was quite low by global standards, even considering the potential sources of upward bias inherent in the data. Therefore, the unusually high level of numeracy in East Asia in the early 21st century was already present in the early modern period. The findings imply that in the Korean case, for example, the foundations of the human-capital based catch-up growth were laid very early. More broadly, we argue that Korea, Japan, and China returned to the growth-path at different points of the 20th century, and this return was pre-determined by their early numeracy development.
urn:nbn:de:bsz:21-opus-67027
Keywords: O15; O40; I21; N35; N30; 330; Human-Capital; Development; Growth; Numeracy